Diffusion Bonding of TiC Cermet to Stainless Steel Using Impulse Pressuring with Ti-Nb Interlayer. Issue 4 (April 2017) - Jia, Li; Guangmin, Sheng
Abstract: Impulse pressuring diffusion bonding (IPDB) of TiC cermet to stainless steel 06Cr19Ni10 using Ti-Nb interlayer was carried out in an attempt to reduce the bonding time and to alleviate the detrimental effect of interfacial reaction products on bonding strength. Successful bonding is achieved at 890 °C under a pulsed pressure of 2∼10 MPa within a duration of only 4∼12 min, which is notably shortened in comparison with conventional diffusion bonding. Microstructure characterization reveals the existence of σ phase with a limit solubility of Nb, ( β -Ti, Nb) phase, and solid solution of Ni in α + β -Ti in the reaction zone. Maximum shear strength of 110 MPa is obtained when the joint is bonded for 10 min, indicating a robust metallurgical bonding is achieved. Upon shear loading, the joints fracture along the remnant Ti/ α + β -Ti interface and extend to the interior of TiC cermet in a brittle cleavage manner. This technique provides a highly promising bonding method of TiC cermet and steel.